Analisis Informasi Anatomi Dengan dan Tanpa Parallel Acquisition Technique Menggunakan Sekuen 2D Thick Slab Single Shot Fast Spin Echo pada Pemeriksaan Magnetic Resonance Cholangiopancreatography (MRCP) - Rismawati Dian Aretnasih; Lidya Purna WS Kuntjoro; Siti Masrochah (Poltekkes Kemenkes Semarang, 2015)
Backgroud: 2D thick slab single shot fast spin echo (SSFSE) sequence in MRCP examination is a sequence of fast spin echo (FSE) which has a long turbo factor so that the time of acquisition in this sequence is longer than usual that will potentially cause image blurring. Parallel acquisition or SENSE technique is a technique used to reduce acquisition time and improve spatial resolution. The purpose of this study was to determine differences in anatomical information with and without parallel acquisition technique in 2D thick slab SSFSE sequences on MRCP examination.Methods: This research was an experimental study. This research was conducted by Philips 1.5 T MRI unit in dr. S Hardjolukito Yogyakarta Hospital. Data were 20 MRCP images from 10 normal volunteers with and without parallel acquisition technique on sequences of 2D thick slab SSFSE. Assessment of the images was conducted qualitatively in the form of respondents's assessment of the clearance of anatomical information includes the gallbladder, right hepatic duct, left hepatic duct, common bile duct, common hepatic duct, cystic duct, and the main pancreatic duct. Quantitative data analyzed by Cohen's Kappa test, cross tabulation, and Wilcoxon tests.Results: The result showed that there was a difference between the clearance of the overall anatomical information between 2D thick slab SSFSE sequences with and without parallel acquisition technique in MRCP with p = 0.000 (p-value 0.05), based on the mean rank obtained sequences of 2D thick slab SSFSE SENSE (14.50) better than the 2D thick slab SSFSE (0.00). Analysis of each anatomy showed significant differences in all organs except the gallbladder p = 0.059, p = left hepatic duct and the common bile duct 0.059 with p = 0.08.Conclusion: Parallel acquisition technique (SENSE) was well used because it has a faster acquisition time without decreasing image resolution.